Replication of previous genome-wide association studies of HKDC1, BACE2, SLC16A11 and TMEM163 SNPs in a gestational diabetes mellitus case–control sample from Han Chinese population - Tan YX (Dove Medical Press, 2019)
Yi-Xiong Tan,1 Shi-Min Hu,2–4 Yi-Ping You,5 Gui-Lian Yang,6 Wei Wang11Department of Radiology, The Third Xiangya Hospital of Central South University, Changsha, Hunan 410013, People’s Republic of China; 2Department of Epidemiology and Health Statistics, Xiangya School of Public Health, Central South University, Changsha, Hunan 410078, People’s Republic of China; 3Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing 100053, People’s Republic of China; 4Beijing Key Laboratory of Neuromodulation, Beijing 100053, People’s Republic of China; 5Department of Obstetrics and Gynecology, Hunan Provincial Hospital of Maternal and Child Health, Changsha, Hunan 410008, People’s Republic of China; 6Nutrition Department, Hunan Provincial Hospital of Maternal and Child Health, Changsha, Hunan 410008, People’s Republic of ChinaBackground: Four novel glucose metabolism risk loci (HKDC1 rs4746822, BACE2 rs6517656, SLC16A11 rs13342232 and TMEM163 rs998451) were identified in recent genome-wide association studies (GWAS) of Afro-Caribbean, European, Hispanic, Thai, Mexican, Latin American and Indian populations. None of the abovementioned SNPs has been reported in a Han Chinese population.Aim: To replicate the relationships between HKDC1 rs4746822, BACE2 rs6517656, SLC16A11 rs13342232 and TMEM163 rs998451 with gestational diabetes mellitus (GDM) in a Han Chinese population.Methods: This was a case–control study which enrolled 334 pregnant women with GDM and 367 pregnant women with normal glucose tolerance. The linear regression and logistic regression were used to estimate the association between SNPs with the risk of GDM, HOMA-IR and fasting insulin levels. The fasting insulin concentration and HOMA-IR were log10 transformed before analysis.Results: No significant differences in the alleles and genotypes of SLC16A11 rs13342232, HKDC1 rs4746822 and BACE2 rs6517656 were observed between cases and controls. After adjusting the weekly BMI growth, pre-pregnancy BMI and maternal age, under the additive model, SLC16A11 rs13342232 was associated with log10fasting serum insulin (Beta=0.046, p=0.016), log10HOMA-IR level (Beta=0.061, p=0.003) and fasting plasma glucose level (Beta=0.164, p=0.011); HKDC1 rs4746822 was associated with OGTT 2-hr plasma glucose level (Beta=0.239, p=0.016); and BACE2 rs6517656 was associated with log10fasting serum insulin (Beta=−0.053, p=0.044) and log10HOMA-IR level (Beta=−0.060, p=0.048). After correction for multiple testing, the associations of SLC16A11 and HKDC1 with glucose metabolism remained statistically significant. The A allele of TMEM163 rs998451 was not detected in this population.Conclusion: HKDC1 rs4746822, BACE2 rs6517656 and SLC16A11 rs13342232 are associated with glucose metabolism in pregnant women of Han Chinese.Keywords: gestational diabetes mellitus, SLC16A11, HKDC1, BACE2, TMEM163